Citation Concept Analysis (CCA) of concepts introduced by Pierre Bourdieu: Measuring their impact across fields and periods - Bornmann Lutz; Crothers Charles; Haunschild Robin (Journal of Data and Information Science)
Citations can be used in evaluative bibliometrics to measure the impact of papers. However, citation analysis can be extended by a multi-dimensional perspective on citation impact which is intended to receive more specific information about the kind of received impact.